The Decision Support System of Grade Promotion For The Students At Islamic Boarding School Foundation Tahfidzul Qur'an Mathlaul Huda Using Analytic Hierarchy Process Method - Sri Ipnuwati; Jamaludin Jamaludin; Sri Surya Mandala (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Decision support system is the system which is very helpful for decision-maker through data processing and decision model in solving a problem which is semi-structured or unstructured. In determining whether the student will graduate or stay in the class, it is necessary to pay attention to the thing which greatly affects the student activity. In this research, there are five assessment criteria used, namely Memorization, Semester Value, Morals, Imlak, and Reading the Alkitab. There are ten alternatives used, and in this research, the range of values used for graduating students is> 29.99, so that the results obtained by the 9th student alternative and the 10th student alternative stay in the class because the value is <29.99. This objective assessment, hopefully, it can help the teachers, ustadz and kiyai in assessing students who have extraordinary potential, so that students can find out their abilities and potential both in the academic and non-academic fields.